2020
DOI: 10.1021/acs.jpcc.0c04492
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Carbon Tetrachloride on Gold Surfaces

Abstract: Banned for already 20 years, carbon tetrachloride is still used industrially. The ingestion of the halogen compound (inhalation, dermal contact, drinking) is known to induce serious damage to the liver, for which gold particles might represent one of the most efficient treatment. Here, using the temperature-programmed desorption technique, we show that carbon tetrachloride is decomposed by a polycrystalline gold surface producing Cl 2 at a minimum rate of 25% of the deposited molecules. The adsorption and deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…It was recently reported that CCl 4 produces Cl 2 on a polycrystalline gold surface. 22 To determine the influence of CCl 4 , AuNPore was analysed by X-ray photoelectron spectroscopy (XPS) and the survey spectra of the following three samples are shown in Fig. 3A: (a) fresh catalyst, (b) used catalyst before washing, and (c) refreshed catalyst after washing with H 2 O 2 /NaOH.…”
mentioning
confidence: 99%
“…It was recently reported that CCl 4 produces Cl 2 on a polycrystalline gold surface. 22 To determine the influence of CCl 4 , AuNPore was analysed by X-ray photoelectron spectroscopy (XPS) and the survey spectra of the following three samples are shown in Fig. 3A: (a) fresh catalyst, (b) used catalyst before washing, and (c) refreshed catalyst after washing with H 2 O 2 /NaOH.…”
mentioning
confidence: 99%